2010
DOI: 10.1063/1.3455198
|View full text |Cite
|
Sign up to set email alerts
|

Short vertical tube furnace for the fabrication of doped glass microsphere lasers

Abstract: Access to the full text of the published version may require a subscription. We report on the design of an electric tube furnace that can be used for the fabrication of doped glass microsphere lasers. The tube furnace has a short hot zone of length 133 mm and is based on a quartz tube design. Doped laser glass particles, specifically Er:Yb phosphate glass ͑IOG-2͒, of ϳ1 m diameter are blown into the furnace using a 60 ml syringe and microspheres ranging in size from 10 to 400 m are collected at the output of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…One method involves making a single cavity by drawing out a glass wire from a piece of doped glass and melting the tip of the wire to form a spherical resonator 1 . Alternatively, many spherical resonators can be made simultaneously by passing particles of doped glass through a furnace 2 3 . Both of these methods are tedious; in the first case, only one resonator can be made at a time.…”
mentioning
confidence: 99%
“…One method involves making a single cavity by drawing out a glass wire from a piece of doped glass and melting the tip of the wire to form a spherical resonator 1 . Alternatively, many spherical resonators can be made simultaneously by passing particles of doped glass through a furnace 2 3 . Both of these methods are tedious; in the first case, only one resonator can be made at a time.…”
mentioning
confidence: 99%
“…Chalcogenide glass microspheres have also been made using a 1-metre long vertical tube furnace [32], whereby crushed glass powder was initially sieved to obtain the required particle size. Recently, Ward et al [33] reported on the design of a short (133 mm) electric tube furnace that can be used for the fabrication of glass microspheres. In this setup a right-angle injection system was designed to blow the glass powder safely into the heated area and to overcome the chimney effect, see …”
Section: Microsphere Fabricationmentioning
confidence: 99%
“…This is extremely important for chalcogenide glass introduced in the previous section. Therefore, a powder floating method has been proposed [ 72 , 73 ], which is not only capable of producing microspheres of different sizes at the same time, but also effectively avoids the introduction of impurities.…”
Section: Fabrication Of Compound Glass Microspheresmentioning
confidence: 99%